Developing Upak Nyamu Ethnomathematics Learning Media through Design-Based Research to Improve Elementary Students’ Critical Thinking - Rita Rita; Krisma Natalia; Ika Fitri Apriani P (Journal of Educational Sciences, 2026)
The limited integration of local cultural contexts into mathematics instruction remains a significant gap, particularly in elementary education, where learning often emphasizes abstract concepts that are not connected to students’ real-life experiences. In addition, the availability of culturally based learning media that are both contextually relevant and empirically tested is still limited. This condition reduces student engagement and constrains the development of higher-order thinking skills. Therefore, this study aims to develop and examine the effectiveness of culturally based learning media using upak nyamu to enhance elementary students’ critical thinking skills and support meaningful learning experiences. This study employed a Design-Based Research (DBR) approach involving 28 fourth-grade students. Data were collected through expert validation, observations, interviews, and pretest–posttest assessments. The results indicate that the developed media is valid and feasible, with a Content Validity Index exceeding 0.80 across all aspects. Students’ mean scores increased from 9.71 to 17.04, while the N-Gain score (0.0799) remained in the low category due to the short implementation period and the need for sustained use of ethnomathematics-based media. The findings show that integrating local cultural elements into mathematics learning enhances students’ understanding, engagement, and cultural awareness, and highlights the importance of culturally responsive pedagogy in creating meaningful and contextual learning environments.